PENGARUH BERBAGAI AMELIORAN DAN KONSENTRASI PUPUK MIKRO PADA TANAMAN EDAMAME (Glycine max (L.) Merill) DI TANAH GAMBUT - Nicco Yanuar; Radian; Iwan Sasli; Riko Prasetyo (BPFP Universitas Bengkulu, 2025)
[THE EFFECT OF VARIOUS SOIL AMELIORANTS AND MICRONUTRIENT FERTILIZER CONCENTRATIONS ON EDAMAME (Glycine max (L.) Merill) PLANTS IN PEAT SOIL]. The cultivation of edamame (Glycine max (L.) Merrill) in Indonesia remains limited, despite increasing demand in both domestic and export markets. However, peat soils present challenges for edamame production due to their high acidity and nutrient deficiencies. This study aimed to evaluate the effects of different soil amendments and micronutrient fertilizer concentrations on the growth and yield of edamame cultivated in peat soil. The research was conducted from March to May 2023 at the Agribusiness Technical Implementation Unit (UPT) of the Pontianak City Agriculture and Food Security Office. A factorial completely randomized design (CRD) was employed, with the first factor being the type of soil amendment (chicken manure, cow manure, and oil palm bunch compost) and the second factor being micronutrient fertilizer concentrations (0 g/L as control, 0.100 g/L, 0.125 g/L, 0.150 g/L, and 0.175 g/L). Results indicated that the interaction between soil amendments and micronutrient fertilizer concentrations had no significant effect on all measured variables. Soil amendments alone had a significant effect on plant height at two and three weeks after planting, but not at four weeks, nor on branch number or plant dry weight. Conversely, micronutrient fertilizer concentration significantly influenced plant dry weight only. These findings suggest that while soil amendments support early vegetative growth, micronutrient fertilizers primarily enhance biomass accumulation. The study provides practical insights for optimizing fertilization strategies to improve edamame cultivation on peat soils.